Memahami ACFTA dari Perspektif Masyarakat Jaringan - Muhtar Habibi (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2011)
This paper tries to explain the ACFTA from the perspective of the network society. This paper argues, the establishment of ACFTA is an effort to expand capital in Cina-ASEAN region which is supported by both MNC and a network of political-economic elites who embrace neo-classical paradigm, especially export-oriented industrialization strategy. The development of Information and Communication Technology (ICT) has enabled the implementation of the MNCs global production using global commodity chain. At the same time, political elites need the flow of capital to boost exports and spur economic growth. They believe that everything that can attract foreign investment needs to be done. One of them is to eliminate trade barriers and create stability in the region to ensure smooth production of foreign investors. Cooperation between the MNC with the political economic elites in both regions finally managed to encourage the formation of ACFTA. Under such a condition, inequality between economic and political elites on one hand, and the masses, on the other in the two regions widened. Political economic elites in both regions are embodied in the dominant network to enjoy more fruits of growth, while the mass largely enjoy just the remainder of the development cake. Today, the gap is not only evident between countries, but also between networks of people. Only by establishing and strengthening alternative networks, can the exploitative effects of dominant networks be minimized.Keywords: ACFTA, network society, export-oriented industrialization, inequality, alternative network